(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2021)
The incidence of extended spectrum beta-lactamase (ESBL)-producing pathogens is worrisome because it confers multiple drug resistance (MDR). Considering their serious clinical significance, the study investigated the prevalence of MDR-ESBL-producing Salmonella strains isolated from raw chicken meat in Southern Nigeria. A total of 240 raw chicken meat were sampled and the recovered Salmonella strains were characterized for MDR and ESBL-genes using Kirby Bauer disc diffusion and molecular techniques. Of the 52 confirmed Salmonellaenterica serotypes, 67.31% (35/52) were Salmonella entericasubsp. entericaserovar Typhimurium, 32.68% (17/52) were Salmonella entericasubsp. entericaserovar Enteritidis, 78.85% (41/52) were ESBL-producer and 88.45% (46/52) multidrug resistant. Ampicillin (96.15%) and gentamycin (40.39%) were the most and least antibiotics. The most prevalent MDR-ESBL-genes were bla CTX-M (92.68%), followed by bla SHV genes (68.29%) and bla TEM(31.71%). This study showed that Salmonella serotypes with high ESBL-genes and MDR were prevalent in raw chicken meat vended in southern Nigerian markets. Bangladesh J. Sci. Ind. Res.56(4), 271-284, 2021